Atomoxetine reverses locomotor hyperactivity, impaired novel object recognition, and prepulse inhibition impairment in mice lacking pituitary adenylate cyclase-activating polypeptide. (25th June 2015) - Shibasaki, Y.; Hayata-Takano, A.; Hazama, K.; Nakazawa, T.; Shintani, N.; Kasai, A.; Nagayasu, K.; Hashimoto, R.; Tanida, M.; Katayama, T.; Matsuzaki, S.; Yamada, K.; et al.
Highlights: ATX significantly alleviated ADHD-related behavioral abnormalities of PACAP − / − mice. ATX significantly alleviated impaired prepulse inhibition in PACAP −/− mice. The ATX-induced increase in extracellular DA and NA levels were higher in PACAP −/− mice compared to wild-type mice. PACAP −/− mice are an ideal rodent model for the study of ADHD etiology and drug development. Abstract: Attention-deficit/hyperactivity disorder (ADHD) is a complex neurobehavioral disorder that is characterized by attention difficulties, impulsivity, and hyperactivity. A non-stimulant drug, atomoxetine (ATX), which is a selective noradrenaline reuptake inhibitor, is widely used for ADHD because it exhibits fewer adverse effects compared to conventional psychostimulants. However, little is known about the therapeutic mechanisms of ATX. ATX treatment significantly alleviated hyperactivity of pituitary adenylate cyclase-activating polypeptide (PACAP)-deficient (PACAP −/− ) mice with C57BL/6J and 129S6/SvEvTac hybrid background. ATX also improved impaired novel object recognition memory and prepulse inhibition in PACAP −/− mice with CD1 background. The ATX-induced increases in extracellular noradrenaline and dopamine levels were significantly higher in the prefrontal cortex of PACAP −/− mice compared to wild-type mice with C57BL/6J and 129S6/SvEvTac hybrid background. These results suggest that ATX treatment-induced increases in central monoamine metabolism may be involved in the rescue of ADHD-related abnormalities in PACAP −/− mice. Our current study suggests that PACAP −/− mice are an ideal rodent model with predictive validity for the study of ADHD etiology and drug development. Additionally, the potential effects of differences in genetic background of PACAP −/− mice on behaviors are discussed.